2010
DOI: 10.1089/cyber.2009.0142
|View full text |Cite
|
Sign up to set email alerts
|

The Neural and Psychological Basis of Herding in Purchasing Books Online: An Event-Related Potential Study

Abstract: In this study, event-related brain potentials (ERPs) were used to investigate the neural and psychological bases of consumer herding decision in purchasing books online. Sixteen participants were asked to decide as quickly as possible whether to buy a book on the basis of its title keywords and the numbers of positive and negative reviews in stimulus. The given title keywords were very similar, and participants did not have special preference for any particular one. Hence, they were forced to adopt the strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 34 publications
2
47
1
Order By: Relevance
“…The LPP is sensitive to the motivation and emotional valence, reflecting the attitudes of the consumers (Ma et al, 2018). It is worth noting that the LPP reflects a cognitive process of categorizing assessment in the later decision stages (Jin et al, 2015;Chen et al, 2010). For the stereotype of the brands in different categories, when the personality evaluations of brand names are consistent with its categorizing criterion (or the expectation), we suspect that obvious evaluative priming occurred in addition to semantic priming.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The LPP is sensitive to the motivation and emotional valence, reflecting the attitudes of the consumers (Ma et al, 2018). It is worth noting that the LPP reflects a cognitive process of categorizing assessment in the later decision stages (Jin et al, 2015;Chen et al, 2010). For the stereotype of the brands in different categories, when the personality evaluations of brand names are consistent with its categorizing criterion (or the expectation), we suspect that obvious evaluative priming occurred in addition to semantic priming.…”
Section: Introductionmentioning
confidence: 90%
“…Electrode impedance was kept below 5 kΩ. A 16 Hz (24 dB/octave) digital low pass filter was applied off-line to the continuous EEG data (Jin et al, 2015;Chen et al, 2010). Trials with peak-to-peak deflections exceeding ±100 µV and other artifacts were excluded using BrainVision Analyzer 2.1 software.…”
Section: Electroencephalogram (Eeg) Recording and Analysismentioning
confidence: 99%
“…ERPs were constructed by separately averaging three picture types (positive, neutral, and negative). The following nine electrodes (C1, Cz, C2, CP1, CPz, CP2, P1, Pz, P2) were selected for statistical analysis (Chen et al, 2010). Fig.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…P2 was found to peak approximately 200 ms after the onset of stimuli and was mainly distributed in the frontal area (Crowley and Colrain, 2004;Polezzi et al, 2008). P2 is an attention-related component, reflecting early rapid automatic activity (Crowley and Colrain, 2004;Polezzi et al, 2008), and an enhanced P2 reflects the engagement of attentional resources (Carretié et al, 2001;Chen et al, 2010;Bublatzky and Schupp, 2012). Furthermore, it has been reported that negative stimuli can engage more attentional resources compared to positive stimuli, resulting in negative stimuli that induce larger P2 amplitudes than positive stimuli (Carretié et al, 2001;Huang and Luo, 2006;Thomas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In previous consumer neuroscience studies, P2 and LPP are two ERP components that have always been used to examine consumers' evaluations of marketing stimuli (Carretié et al, 2001;Chen et al, 2010;Bublatzky and Schupp, 2012). P2 was found to peak approximately 200 ms after the onset of stimuli and was mainly distributed in the frontal area (Crowley and Colrain, 2004;Polezzi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%